Fucoxanthin and Astaxanthin-Production, Biofunction, and Application - Hosokawa, Masashi; Maeda, Hayato (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Fucoxanthin and Astaxanthin-Production, Biofunction, and Application" focuses on the research of marine fucoxanthin and astaxanthin and contains two reviews, ten articles, and one communication.